5PSQ-107 Securising of tisagenlecleucel thawing and delivering. (23rd March 2022) - Benjamin, F; Du Repaire, T; Sicard, G; Ausias, N; Montana, M; Gauthier Villano, L; Pourroy, B
Abstract : Background and importance: Tisagenlecleucel is available in 50 mL and 250 mL frozen bags (containing 10–30 mL and 30–50 mL cell suspension, respectively). Tisagenlecleucel should be thawed at 37° C then infused within 30 min to maintain cell viability. Thawing time according to volumes is a critical point which is not known. Aim and objectives: We evaluated in this work the thawing times of tisagenlecleucel according to volumes. Material and methods: Ethylene vinyl acetate empty infusion bags were provided by Novartis. Freezing tisagenlecleucel matrix was reconstituted. Empty bags (50 mL and 250 mL) were respectively filled with 10 and 20 mL and 30, 40 and 50 mL of reconstituted matrix, then frozen at –150°C. To mimic real conditions, they were placed into a second sterile bag and thawed in a water bath at +37°C. To evaluate thawing duration, volume of remaining icicles was calculated by multiplying surface (GeoToolsoftware) by thickness (measured with a caliper). Furtheremore, the time to deliver the bags was measured by two different operators in triplicate. Results: 124±5 s and 191±30 s were necessary to achieve complete thawing of 50 mL bags filled at 10 and 20 mL, respectively. 155±16 s, 221±12 s and 240±6 s were needed to achieve complete thawing of 250 mL bags filled at 30, 40 and 50 mL, respectively. For a type of bag, decreasing volumes thawed faster, but 50 mL bags filled at 20 mL took longer to thaw than 250 mL bags filled at 30 mL (different spatial conformation and specific surfaces). Delivery of thawed bags from the pharmacy to the transplant unit was done in 4.5±0.21 min. Conclusion and relevance: Thawing duration may vary by twice a function of volume. Mean lengths provide an optimal organisation in a circuit where every minute must be taken into account. A total thawing-addressing time rate of between 6.5 and 8.5 min means that the nursing team has almost 20 min to administer tisagenlecleucel. References and/or acknowledgements: Conflict of interest: No conflict of interest